2020
DOI: 10.1182/blood-2020-140161
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients (pts) with Chronic Myeloid Leukemia (CML): Results from the International CML Foundation (iCMLf) CML and COVID-19 (CANDID) Study

Abstract: Background Comorbid conditions, including solid and hematologic malignancies, may impact risk of contracting SARS CoV-2 or having severe COVID-19. Data specific to individual cancer types is essential to differentiate impact of patient, disease, and therapy specific factors on risk and outcomes, as the pandemic remains uncontrolled. Goal The primary goal of the CANDID study was to rapidly collect and analyze information on COVID-19 cases among CML pts to define prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 0 publications
1
34
2
4
Order By: Relevance
“…During the pandemic, although the likelihood of developing a COVID-19 infection in persons with CML is very low ( 28 31 ), negative impact on different aspects of CML management including TKI therapy response monitoring, TKI therapy, and enrollment in and compliance with clinical trials is also reported ( 29 ). These highlighted the importance of adequate access to health care services such as patient education of having appropriate personal self-protection equipment, establishing a safe area in the hospital or clinic, and telemedicine and mailed medicine to avoid monitoring and therapy interruptions 1 , 2 , 3 ( 44 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pandemic, although the likelihood of developing a COVID-19 infection in persons with CML is very low ( 28 31 ), negative impact on different aspects of CML management including TKI therapy response monitoring, TKI therapy, and enrollment in and compliance with clinical trials is also reported ( 29 ). These highlighted the importance of adequate access to health care services such as patient education of having appropriate personal self-protection equipment, establishing a safe area in the hospital or clinic, and telemedicine and mailed medicine to avoid monitoring and therapy interruptions 1 , 2 , 3 ( 44 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IES-R (range, 0-88) was used to assess subjective distress (excessive panic and anxiety) caused by traumatic events including traumarelated distressing memories and persistent negative emotions resulting from the pandemic, which is composed of three subscales to measure the avoidance, intrusion, and hyper-arousal. The total IES-R score was categorized as follows: subclinical (0-8), mild (9-25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), and severe (44-88) (37). Respondents who had the scores greater than the cutoff threshold of 10 in PHQ-9, 10 in GAD-7, and 26 in IES-R indicate moderate to severe depression, anxiety, and distress, respectively, and IES-R score ≥ 26 is associated with post-traumatic stress disorder (PTSD) symptoms (35,38,39).…”
Section: Assessment Of Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which immunocompromised patients are able to mount a ‘normal’ immune response to SARS‐CoV‐2 remains unknown. Collaborative cohort analyses reporting clinical sequelae following SARS‐CoV‐2 infection in patients with either a classical ‘Philadelphia Chromosome’ negative myeloproliferative neoplasm (MPN) or chronic myeloid leukaemia (CML) have recently been published 2,3 . Outcomes were varied but, to date, older patients, those with myelofibrosis (MF) and those who had sudden discontinuation of the Janus kinase (JAK) inhibitor (JAKi) ruxolitinib had worse outcomes.…”
Section: Figurementioning
confidence: 99%
“…Higher risks were also identified for ruxolitinib discontinuation following infection. The CANDID CML study reported on 110 patients with SARS‐CoV‐2 infection, 70% of whom were on TKIs 3 . Univariate analysis revealed age >75 years, severe infection and use of imatinib (likely surrogate marker of older age) as adverse risk factors.…”
Section: Figurementioning
confidence: 99%